An Examination of the Association Between Gender and Reporting Intentions for Fraudulent Financial Reporting - Kaplan, Steven E.; Pany, Kurt 1946-; Samuels, Janet; Zhang, Jian (2009)
We report the results of a study that examines the association between gender and individuals’ intentions to report fraudulent financial reporting using non-anonymous and anonymous reporting channels. In our experimental study, we examine whether reporting intentions in response to discovering a fraudulent financial reporting act are associated with the participants’ gender, the perpetrator’s gender, and/or the interaction between the participants’ and perpetrator’s gender. We find that female participants’ reporting intentions for an anonymous channel are higher than for male participants; the fraud perpetrator’s gender and the interaction with participants’ gender were not significantly associated with anonymous channel reporting intentions. Neither of the two factors nor the interaction between the two factors was associated with reporting intentions to a non- anonymous reporting channel. Results from an additional analysis indicate that male and female participants differ in the extent to which they judge the reduction in personal costs of an anonymous reporting channel compared to a non-anonymous reporting channel and that the reduction in personal costs mediates the relationship between participant gender and anonymous reporting intentions.
Keywords: non-anonymous reporting channel; Anonymous reporting channel; fraudulentreporting; Gender; Whistleblowing